2010
DOI: 10.1038/ajh.2009.246
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea, Masked Hypertension, and Arterial Stiffness in Men

Abstract: Patients with OSA presented a higher unadjusted rate of masked hypertension than matched controls. Lowest oxygen saturation has an independent association with arterial stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
1
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 28 publications
3
61
1
8
Order By: Relevance
“…45 A subsequent study by the same group examined arterial stiffness in OSA patients with and without masked hypertension. 46 It was found that, whereas both types of OSA patients showed significantly higher arterial stiffness as compared to healthy controls, OSA patients with masked hypertension had the highest arterial stiffness. Chung et al 47 compared cfPWV in patients with mild to moderate OSA, severe OSA and control subjects.…”
Section: Resultsmentioning
confidence: 96%
“…45 A subsequent study by the same group examined arterial stiffness in OSA patients with and without masked hypertension. 46 It was found that, whereas both types of OSA patients showed significantly higher arterial stiffness as compared to healthy controls, OSA patients with masked hypertension had the highest arterial stiffness. Chung et al 47 compared cfPWV in patients with mild to moderate OSA, severe OSA and control subjects.…”
Section: Resultsmentioning
confidence: 96%
“…Because obesity and insulin resistance tend to accompany OSA as comorbidities, it has been difficult to isolate the independent effect of OSA and its treatments on the development and consequences of hypertension. Several studies have postulated that increased sympathetic tone and endothelial dysfunction cause hypertension in OSA 8, 9, 10…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have revealed higher PWV in obstructive sleep apnoea (OSA) patients than in controls and reported nocturnal oxygen desaturation to be associated with high PWV 19, 20…”
Section: Introductionmentioning
confidence: 99%